An efficient calibration method for SQUID measurement system using three orthogonal Helmholtz coils - 李华 张树林 张朝祥 孔祥燕 谢晓明 (Chinese physics B, 2016)
For a practical superconducting quantum interference device（SQUID） based measurement system,the Tesla/volt coefficient must be accurately calibrated.In this paper,we propose a highly efficient method of calibrating a SQUID magnetometer system using three orthogonal Helmholtz coils.The Tesla/volt coefficient is regarded as the magnitude of a vector pointing to the normal direction of the pickup coil.By applying magnetic fields through a three-dimensional Helmholtz coil,the Tesla/volt coefficient can be directly calculated from magnetometer responses to the three orthogonally applied magnetic fields.Calibration with alternating current（AC） field is normally used for better signal-to-noise ratio in noisy urban environments and the results are compared with the direct current（DC） calibration to avoid possible effects due to eddy current.In our experiment,a calibration relative error of about 6.89 × 10-4is obtained,and the error is mainly caused by the non-orthogonality of three axes of the Helmholtz coils.The method does not need precise alignment of the magnetometer inside the Helmholtz coil.It can be used for the multichannel magnetometer system calibration effectively and accurately.